(untitled) - Waugh, Troy (Hoboken, N.J., 2005)
This updated Second Edition demonstrates how combining the power of trust with the power of persuasion can help CPAs sell their services more effectively. Each chapter develops a key concept of marketing or selling that's easy to follow and shows how to apply the concepts to any CPA practice. Through a step-by-step approach to developing and mastering a stronger marketing and sales presence, this book focuses on how to dramatically enhance the reader's growth potential. It presents real-world examples from top CPA rainmakers and other marketing and management gurus, including Tom Peters. This updated second edition offers interviews covering Sarbanes-Oxley and the new accounting rules
Keywords: Selling,Quản trị kinh doanh,Marketing,Strategic planning,Customer relations; Decision making,Management